Ozone concentration measurements. State of the art. (Ozone Therapy Global Journal, 2011)
There is a wide interest regarding how to accurately measure the ozone concentrationin agas mixture. Concerns are even more relevant regarding ozone medical applicationsbecause outcomes greatly depend on the correct administered dosages.